Current Concepts in General Thoracic Surgery - Cagini, Lucio (IntechOpen, 2012)
The Aim of "Current Concepts of General Thoracic Surgery" is to provide a brief overview of several topics in this field. It includes a collection of contributions from many outstanding Authors who provide their knowledge and experience from many countries around the world. We apologize for the chapters reviewed that have were not chosen for publication in this book; however, according to the single centres experience, the final result offers thorough and precious information on the several topics evaluated by the Authors. The wide range of subjects discussed goes from CT assessment of solitary pulmonary and metastatic nodules to prospective studies of drug delivery in thoracic surgery including surgical risk prediction, stress reaction, robotic pulmonary and cardiac procedures, vascular and thoracic reconstruction techniques, thoracic trauma and mediastinal fistula. I believe that this book represents an enhancement in the knowledge and in the involvement of individuals dedicated to these areas of study. It is my duty and pleasure to thank colleagues who helped me in the interesting and stimulating review process; Dr. Stefano Pasquino for cardiac surgery and Professor Francesco Puma for his many worthwhile suggestions.